2017
DOI: 10.1080/14786419.2016.1272105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth regulators on callus induction and secondary metabolite production in Cuminum cyminum

Abstract: Cumin (Cuminum cyminum) is an annual plant from Apiaceae family that is cultivated in Iran as landraces. The most important chemical composition of the cumin essential oil was cuminaldehyde. In this research, the effect of different landraces and growth regulators was evaluated on callus induction, and best callus was used for amount of cuminaldehyde content. Node, root, leaf and hypocotyl explant from seedlings of Birjand and Qaen landraces were cultured on MS and MS5 medium supplemented with different concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The influence of different concentrations and combinations of growth regulators on the induction of callus from capitula of Pulicaria incisa showed a better response in the medium supplemented with 2,4D and KIN. 70% was the higher callus rate obtained onto 2.4D 4.10 -5 M and KIN 5.10 -6 M. The same observations have been noted by Gupta et al (2015) and Farvardin et al (2017) who confirmed the effectiveness of 2.4D/KIN in vitro conditions by the best induction and proliferation of callus masses in dicotyledonous plants.…”
Section: Discussionsupporting
confidence: 83%
“…The influence of different concentrations and combinations of growth regulators on the induction of callus from capitula of Pulicaria incisa showed a better response in the medium supplemented with 2,4D and KIN. 70% was the higher callus rate obtained onto 2.4D 4.10 -5 M and KIN 5.10 -6 M. The same observations have been noted by Gupta et al (2015) and Farvardin et al (2017) who confirmed the effectiveness of 2.4D/KIN in vitro conditions by the best induction and proliferation of callus masses in dicotyledonous plants.…”
Section: Discussionsupporting
confidence: 83%
“…The auxins initiate cell division and control the processes of growth and cell elongation because they induce the transcription of mRNA (microRNA) encoding proteins important for growth [ 33 ]. It is often reported that 2,4-D (2,4-dichlorophenoxyacetic acid) is the most suitable auxin for callus initiation and proliferation [ 34 , 35 , 36 , 37 ]. The cytokinins regulate many cellular processes, but the control of cell division is central to the growth and development of medicinal plants [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The e cient callus induction in auxin treated medium is due to initiation of cell division, growth, and elongation; especially promoting microRNA transcription speci c to growth related protein synthesis(George et al 2008). Moreover, it is often cited that 2,4-D is a foremost suitable auxin speci c to callus induction (Anjusha and Gangaprasad 2017;Farhadi et al 2017;Farvardin et al 2017).…”
mentioning
confidence: 99%